The potential of retinoic acid receptors as prognostic biomarkers and therapeutic targets in gastric cancer - Garattini, Silvio Ken; Basile, Debora; De Re, Valli’; Brisotto, Giulia; Miolo, Gianmaria; Canzonieri, Vincenzo; Aprile, Giuseppe; Corvaja, Carla; Buriolla, Silvia; Garattini, Enrico; Puglisi, Fabio (Frontiers in Oncology, 2024)
Background Gastric cancer is a heterogeneous collection of tumors characterized by low survival rates. All-trans retinoic acid (retinoic-acid) is a clinically useful therapeutic agent belonging to the chemical family of retinoids, which consists of both natural and synthetic derivatives of vitamin-A. Retinoids are essential components of the normal diet and they regulate different physiological processes. From a therapeutic point of view, retinoic-acid is the first example of clinically useful differentiating agent. Indeed, the differentiating properties of this compound have promoted the use of retinoic-acid as a standard of care in Acute-Promyelocytic-Leukemia, a rare form of acute myeloid leukemia. In this study, we determine the RNA expression of the six isoforms of Retinoic-Acid-Receptors (RARα/RARβ/RARγ/RXRα/RXRβ/RXRγ) in view of their potential use as gastric cancer progression markers and/or therapeutic targets. In addition, we evaluate associations between the expression of these receptors and a simplified molecular classification of stomach tumors as well as the clinical characteristics of the cohort of patients analyzed. Finally, we define the prognostic value of the various Retinoic-Acid-Receptors in gastric cancer. Methods In this single institution and retrospective RAR-GASTRIC study, we consider 55 consecutive gastric cancer patients. We extract total RNA from the pathological specimens and we perform a NanoString Assay using a customized panel of genes. This allows us to determine the expression levels of the RAR and RXR mRNAs as well as other transcripts of interest. Results Our data demonstrate ubiquitous expression of the RAR and RXR mRNAs in gastric cancers. High levels of RARα, RARβ, RXRα and RXRβ show a significant association with stage IV tumors, “de novo” metastatic disease, microsatellite-stable-status, epithelial-to-mesenchymal-transition, as well as PIK3CA and TP53 expression. Finally, we observe a worse overall-survival in gastric cancer patients characterized by high RARα/RARβ/RARγ/RXRβ mRNA levels. Conclusions In gastric cancer, high expression levels of RARα/RARβ/RARγ/RXRβ transcripts are associated with poor clinical and molecular characteristics as well as with reduced overall-survival. Our data are consistent with the idea that RARα, RARβ, RARγ and RXRβ represent potential prognostic markers and therapeutic targets of gastric cancer.